Osteochondral Lesions of the Tibial Plafond and Ankle Instability With Ankle Cartilage Lesions: Proceedings of the International Consensus Meeting on Cartilage Repair of the Ankle. (March 2022) - Dahmen, Jari; Bayer, Steve; Toale, James; Mulvin, Conor; Hurley, Eoghan T.; Batista, Jorge; Berlet, Gregory C.; DiGiovanni, Christopher W.; Ferkel, Richard D.; Hua, Yinghui; Kearns, Stephen; Lee, Jin Woo; et al.
Background: An international consensus group of experts was convened to collaboratively advance toward consensus opinions based on the best available evidence on key topics within cartilage repair of the ankle. The purpose of this article is to present the consensus statements on osteochondral lesions of the tibial plafond (OLTP) and on ankle instability with ankle cartilage lesions developed at the 2019 International Consensus Meeting on Cartilage Repair of the Ankle. Methods: Forty-three experts in cartilage repair of the ankle were convened and participated in a process based on the Delphi method of achieving consensus. Questions and statements were drafted within 4 working groups focusing on specific topics within cartilage repair of the ankle, after which a comprehensive literature review was performed and the available evidence for each statement was graded. Discussion and debate occurred in cases where statements were not agreed on in unanimous fashion within the working groups. A final vote was then held. Results: A total of 11 statements on OLTP reached consensus. Four achieved unanimous support and 7 reached strong consensus (greater than 75% agreement). A total of 8 statements on ankle instability with ankle cartilage lesions reached consensus during the 2019 International Consensus Meeting on Cartilage Repair of the Ankle. One achieved unanimous support, and seven reached strong consensus (greater than 75% agreement). Conclusion: These consensus statements may assist clinicians in the management of these difficult clinical pathologies. Level of Evidence: Level V, mechanism-based reasoning.